Wide-angle scanning planar array with quasi-hemispherical-pattern elements - Wang, Ren (Sci Rep, 2017)
A compact quasi-hemispherical-pattern antenna, two linear wide-angle scanning arrays, and a planar wide-angle scanning array are proposed. To increase the field-of-view scanning range of arrays, a compact low-profile antenna with a quasi-hemispherical pattern is introduced firstly. When the ground is infinite, the proposed antenna has a quasi-hemispherical pattern, i.e., an approximately uniform radiation in the upper half space. Afterward, two linear arrays arranged along the length and width of the proposed antenna’s radiation patch are presented. The main beams of the two arrays with 16 active elements can scan from less than −75° to more than +75°. When the linear array element number is 128, the maximum scanning angle can reach 86°. At last, a planar array with 16 × 16 active elements is proposed. In two special planes, xz plane and yz plane, the main beams of the planar array can scan from less than −77° to more than +77° with a gain fluctuation less than 5 dB and a maximum side lobe level (SLL) less than −10 dB. An excellent wide-angle-scanning performance both in linear and planar arrays can be obtained using the proposed method.